Application of a dynamic material balance program to an industrial flotation circuit - C. Bazin; A. R. Trusiak; D. Hodouin (Canadian Institute of Mining, Metallurgy and Petroleum, 1995)
"The On-Stream Analyzer has proven, and is still proving to be, an extremely valuable tool for the control of flotation circuits. This paper examines the possibility of going further in the utilization of the analyzer results by using a real-time material balance program to calculate the mass flow rates within the streams of a circuit for process control, analysis and optimization as well as for the detection of sensor malfunction. The material balance algorithm improves measurements and give good estimates of unmeasured variables during normal operating conditions. The potential and limitations of the method are illustrated using results of an application to the Line 3 flotation circuit of Brunswick Mining and Smelting, New Brunswick.IntroductionThe On-Stream Analyzer (OSA) has gained, over the last two decades, the status of key instrument for the control of flotation plants. The OSA is currently used in almost every sulphide flotation plant and its application in oxide mineral flotation plants isincreasing. Commercial OSAs include a sampling system that collectssamples from various streams of a circuit and exposes thesamples to an X-ray beam. The sample then generates X-ray pulsesthat are converted into assays using multilinear regression programs(Leroux and Franklin, 1994). The estimated assays arepassed to the flotation operators via operator consoles, or to controlloops of various degrees of complexity (McKee, 1991), whichmanipulate reagent addition, aeration rate or froth thickness toensure an adequate operation of the plant. Although this applicationrapidly pays for the purchase of the OSA, one should ask:""Could we get more from the OSA?"""